Hydrogen Sulfide Protects Against Uremic Accelerated Atherosclerosis via nPKCδ/Akt Signal Pathway - Lu, Xiangxue; Li, Han; Wang, Shixiang (Frontiers in Molecular Biosciences, 2021)
Background: Cardiovascular disease is the most common complication and leading cause of death in maintenance hemodialysis patients. Previous studies have found that disorders of cystathionine-gamma-lyase/hydrogen sulfide (CSE/H2S) system in maintenance hemodialysis patients are correlated with the risk of cardiovascular disease. Although the role of CSE/H2S system in UAAS has been preliminarily explored, the molecular mechanism of CSE/H2S is still not systematically elaborated, and the molecular mechanism of nPKCδ and its related signaling pathway in UAAS is still not thoroughly studied. Methods: Forty chronic kidney disease (CHD) patients were studied and the activation of nPKCδ in peripheral blood mononuclear cells (PBMCs) were detected. ApoE-/- mice aged 6 weeks were treated with 5/6 nephrectomy and high-fat diet to make UAAS model. They were divided into Sham group (Sham group), UAAS group (UAAS group), UAAS+L-cysteine group (UAAS+L-cys group), UAAS+sodium hydrosulfide group (UAAS+NaHS group) and UAAS+propargylglycine group (UAAS+PPG group). The UAAS+L-cys group, UAAS+NaHS group and UAAS+PPG group were respectively given L-cys, NaHS and PPG by intraperitoneal injection. The aorta was taken 6 weeks after surgery. Western blot was used to detect the activation of nPKCδ, the phosphorylation of Akt, and the expression of VCAM-1 in the aorta of mice. Results: The membrane translocation of nPKCδ in CHD patients with plaque was higher than that in CHD patients without plaque. The membrane translocation of nPKCδ and the expression of VCAM-1 in UAAS group was higher than sham group, L-cys or NaHS injection could suppress the membrane translocation of nPKCδ and the expression of VCAM-1, but PPG treatment resulted in more membrane translocation of nPKCδ and the expression of VCAM-1 (P<0.05, n=6 per group). Akt phosphorylation in UAAS group was lower than sham group, and L-cys or NaHS injection could suppress the degradation of Akt phosphorylation, but PPG treatment resulted in more decrease in the Akt phosphorylation (P<0.05, n=6 per group). Conclusion: Endogenous CSE/H2S system protected against the formation of UAAS via nPKCδ/Akt signal pathway. The imbalance of CSE/H2S system may participate in the formation of UAAS by affecting the expression of downstream molecule VCAM-1, which may be mediated by nPKCδ/Akt signaling pathway.